Proceedings of the 28th Annual Conference on Computer Graphics and Interactive Techniques 2001
DOI: 10.1145/383259.383271
|View full text |Cite
|
Sign up to set email alerts
|

A signal-processing framework for inverse rendering

Abstract: Realism in computer-generated images requires accurate input models for lighting, textures and BRDFs. One of the best ways of obtaining high-quality data is through measurements of scene attributes from real photographs by inverse rendering. However, inverse rendering methods have been largely limited to settings with highly controlled lighting. One of the reasons for this is the lack of a coherent mathematical framework for inverse rendering under general illumination conditions. Our main contribution is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
424
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(439 citation statements)
references
References 39 publications
(64 reference statements)
6
424
0
Order By: Relevance
“…It is, however, not generic because it depends on a specific situation where the shadow of an object of known shape is projected onto an object also of known shape. Recent work [18,19] done simultaneously to ours [12] demonstrated that a complex lighting model, including multiple lightsources and specular properties, can be recovered given several images of an object for which a 3-D model is available but, unlike in our approach, requires assuming that the lighting is the same in all images.…”
Section: Previous Workmentioning
confidence: 99%
“…It is, however, not generic because it depends on a specific situation where the shadow of an object of known shape is projected onto an object also of known shape. Recent work [18,19] done simultaneously to ours [12] demonstrated that a complex lighting model, including multiple lightsources and specular properties, can be recovered given several images of an object for which a 3-D model is available but, unlike in our approach, requires assuming that the lighting is the same in all images.…”
Section: Previous Workmentioning
confidence: 99%
“…For example, Ramamoorthi et al [72] point out that it is not possible to distinguish between low-frequency texture and lighting effects. They suggest that this ambiguity can only be resolved by using active methods or making assumptions about the expected characteristics of the texture and lighting.…”
Section: State Of the Artmentioning
confidence: 99%
“…Ramamoorthi and Hanrahan [72] used spherical harmonics to describe the reflected light field as a convolution of lighting and reflectance. They present a signal processing framework for a variety of inverse rendering problems under the assumption of known geometry.…”
Section: Inverse Renderingmentioning
confidence: 99%
“…Previous methods have considered inverting the direct reflection equation to acquire lighting and reflectance properties [Marschner 1998;Sato et al 1999;Ramamoorthi and Hanrahan 2001]. [Yu et al 1999] develop an inverse global illumination method for BRDF estimation.…”
Section: Inverse Renderingmentioning
confidence: 99%
“…2 Therefore, we consider projector-based acquisition, that illuminates a single spatial location and records the response, rather than light sources that illuminate the whole object (where F is a low-pass filter, that is not easy to invert for diffuse surfaces [Ramamoorthi and Hanrahan 2001]). For projectorbased acquisition, after geometric calibration, we can use the same parameterization for projection and camera images [Seitz et al 2005].…”
Section: Practical Issuesmentioning
confidence: 99%